The grammatical criticism of Ibn Hisham in the clearest path (Journal of the College of Basic Education, 2022)
Whoever reads the book (Most Clear Paths to Alfiya Ibn Malik) by Ibn Hisham (year 761 AH) He finds in it critical thoughts that require standing with him, so this research came to identify the mentality of Ibn Hisham criticism, the nature of the approach he followed in his criticism, and how he dealt with the opinions of grammarians. The research is based on a preface and two chapters. As for the preface, it dealt with criticism between language and terminology. As for the two studies, The first of them was devoted to Ibn Hisham's approach to criticism, and the second was devoted to the areas of his criticism.